Seed Endophytic Bacteria of Pearl Millet (Pennisetum glaucum L.) Promote Seedling Development and Defend Against a Fungal Phytopathogen - Kumar, Kanchan; Verma, Anand; Pal, Gaurav; Anubha,; White, James F.; Verma, Satish K. (Frontiers in Microbiology, 2021)
Seed endophytic bacteria (SEB) are primary symbionts that play crucial roles in plant growth and development. The present study reports the isolation of seven culturable SEB including Kosakonia cowanii (KAS1), Bacillus subtilis (KAS2), Bacillus tequilensis (KAS3), Pantoea stewartii (KAS4), Paenibacillus dendritiformis (KAS5), Pseudomonas aeruginosa (KAS6) and Bacillus velezensis (KAS7) in pearl millet seeds. All the isolates were characterized for their plant growth promoting activities. Most of the SEB also inhibited the growth of tested fungal phytopathogens in dual plate culture. Removal of these SEB from seeds compromised the growth and development of seedlings however re-inoculation with the SEB (Kosakonia cowanii, Pantoea stewartii and Pseudomonas aeruginosa) restored the growth and development of seedlings significantly. Fluorescence microscopy showed inter and intracellular colonization of SEB in root parenchyma and root hair cells. Lipopeptides were extracted from all three Bacillus spp. which showed strong antifungal activity against tested fungal pathogens. Antifungal lipopeptide genes were also screened in Bacillus spp. After lipopeptide treatment, live-dead staining with fluorescence microscopy along with bright-field and scanning electron microscopy revealed structural deformation and cell death in Fusarium mycelia and spores. Furthermore, the development of pores in the membrane and leakages of protoplasmic substances from cells and ultimately death of hyphae and spores were also confirmed. In microcosm assays, treatment of seeds with Bacillus subtilis or application of its lipopeptide alone significantly protected seedlings from Fusarium sp. infection.